Nociceptive atrophy of the rat soleus muscle induced by bone fracture: a morphometric study - Zacharová, G; Knotková-Urbancová, H; Hník, P; Soukup, T (Journal of applied physiology (Bethesda, Md., 1997)
Reflex atrophy of the soleus muscle induced by ipsilateral metatarsal bone fracture in Sagatal-anesthetized adult male rats was studied by using two-dimensional stereological methods 7 days after the operation. When compared with contralateral solei, the wet weight of the experimental soleus muscles was decreased by approximately 24% and the area of the entire muscle section by approximately 29%. In atrophied solei, the number of type 1 fibers was lower by approximately 8%, resulting in lower total number of fibers (by approximately 6%). This indicates that slow motor units might be more sensitive to nociceptive stimulation. However, with respect to the fiber area, the reflex atrophy induced by metatarsal bone fracture in the rat soleus muscle resembles simple atrophy after 7 days, as the mean muscle fiber area was decreased by approximately 26% with no significant difference between atrophy in type 1 and type 2a fibers (by 27.3 and 23.0%, respectively).
Keywords: svalová atrofie; Muscular Atrophy; Bone and Bones; Rats, Wistar; kosti a kostní tkáň; mužské pohlaví; Rats; potkani Wistar; Muscle, Skeletal; zvířata; Fractures, Bone; kosterní svaly; fraktury kostí; krysa rodu Rattus; Male; Animals